Nisekoi : False love. Vol. 10, Shu's crush - Komi, Naoshi, 1986- (Viz Media, 2015)
"It's hate at first sight when Raku Ichijo first meets Chitoge Kirisake. But much to their chagrin, the two are forced into a false love relationship to keep the peace between their feuding gangster families. When Ms. Kyoko, Rakus homeroom teacher, announces she's quitting to get married, the news causes quite a stir. But for some reason, Raku's best friend Shu seems to be reacting strangely...Also, Chitoge's birthday is drawing near. This year, she really wants to celebrate with Raku. Is that a recipe for disaster?!"--P. [4] of cover.